Transposon Insertion Site Sequencing of Providencia stuartii: Essential Genes, Fitness Factors for Catheter-Associated Urinary Tract Infection, and the Impact of Polymicrobial Infection on Fitness Requirements - Alexandra O. Johnson (American Society for Microbiology, 2020)
ABSTRACT Providencia stuartii is a common cause of polymicrobial catheter-associated urinary tract infection (CAUTI), and yet literature describing the molecular mechanisms of its pathogenesis is limited. To identify factors important for colonization during single-species infection and during polymicrobial infection with a common cocolonizer, Proteus mirabilis, we created a saturating library of ∼50,000 transposon mutants and conducted transposon insertion site sequencing (Tn-Seq) in a murine model of CAUTI. P. stuartii strain BE2467 carries 4,398 genes, 521 of which were identified as essential for growth in laboratory medium and therefore could not be assessed for contribution to infection. Using an input/output fold change cutoff value of 20 and P values of <0.05, 340 genes were identified as important for establishing single-species infection only and 63 genes as uniquely important for polymicrobial infection with P. mirabilis, and 168 genes contributed to both single-species and coinfection. Seven mutants were constructed for experimental validation of the primary screen that corresponded to flagella (fliC mutant), twin arginine translocation (tatC), an ATP-dependent protease (clpP), d-alanine-d-alanine ligase (ddlA), type 3 secretion (yscI and sopB), and type VI secretion (impJ). Infection-specific phenotypes validated 6/7 (86%) mutants during direct cochallenge with wild-type P. stuartii and 3/5 (60%) mutants during coinfection with P. mirabilis, for a combined validation rate of 9/12 (75%). Tn-Seq therefore successfully identified genes that contribute to fitness of P. stuartii within the urinary tract, determined the impact of coinfection on fitness requirements, and added to the identification of a collection of genes that may contribute to fitness of multiple urinary tract pathogens. IMPORTANCE Providencia stuartii is a common cause of polymicrobial catheter-associated urinary tract infections (CAUTIs), particularly during long-term catheterization. However, little is known regarding the pathogenesis of this organism. Using transposon insertion site sequencing (Tn-Seq), we performed a global assessment of P. stuartii fitness factors for CAUTI while simultaneously determining how coinfection with another pathogen alters fitness requirements. This approach provides four important contributions to the field: (i) the first global estimation of P. stuartii genes essential for growth in laboratory medium, (ii) identification of novel fitness factors for P. stuartii colonization of the catheterized urinary tract, (iii) identification of core fitness factors for both single-species and polymicrobial CAUTI, and (iv) assessment of conservation of fitness factors between common uropathogens. Genomewide assessment of the fitness requirements for common uropathogens during single-species and polymicrobial CAUTI thus elucidates complex interactions that contribute to disease severity and will uncover conserved targets for therapeutic intervention.